Determination of biological age in different periods of human ontogenesis - Oleksandr Aghyppo; Yaroslavna Puhach; Valeriy Druz; Yana Zhernovnikova (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to determine the parameters of the standardized assessment of biological age and individual characteristics of its occurrence. Material and Methods: analytical generalization of data of scientific literature, clinical anthropometry of the observed contingent, use of sign semantic spaces. Results: the estimation of biological age, based on the standardized parameters being the basis of organogenesis of morphological and functional, is worked out. Conclusions: passport allows to establish biological development lagging or leading the process of physical development of morphological and functional structures that underlies prenosological forecasting constitutional diseases.